Laberintos teóricos : Caminos sinuosos hacia una definición disciplinar - Tesone, Pablo (2017)
The particular vision that runs through these pages is the result of reflections made during the course in the academy —as a student and teacher— and the development as a professional. It seeks to contribute to the problematization about the discipline, its limits, its teaching, and the professional work in order to be able to give the designers, who are dedicated to solve the problems and to satisfy the needs of the different users in public spaces, a way to understand what they do.